Analysis of Total Quality Management in Improving the Quality of Educational Institutions - Raden Darojah; Abdus Salam DZ; Iman Subasman; Jalaludin; Abdul Karim; Muhamad Ahyat (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
Integrated quality management is a philosophy and methodology that helps institutions manage change and develop their respective agendas to respond to the pressure of external factors. This study aims to analyze the implementation of total quality management in improving the quality of early childhood education institutions. This research uses an analytic qualitative descriptive method. Structured interview techniques for schools, teaching staff, administrative staff, parents, foundation managers, the community, and education practitioners; observation techniques for Cendekia Indramayu kindergarten education institutions; and documentation studies on TQM were used in the data collection process. The sample in the study amounted to 7 people who were purposively selected. The data were then analyzed and tested for validity through the data credibility test, transferability test, dependability test, and confirmability test. The results of this study show that the strategy of improving the quality of the institution is done through optimizing and increasing the empowerment of human resources by utilizing the role of educators to improve the quality of the institution; Improving services in every field by using an easily accessible communication network; Increasing the role of parents by involving them in school programs through School Parenting; and Increasing cooperation and communication with communities, organizations, and government agencies. The results of this study provide theoretical and practical implications for school principals that the use of TQM can improve the quality of the institution if it can be implemented properly in the preparation of the institution's strategy.